(untitled) (Teaching and Learning Inquiry, 2016)
While the model of students and staff working in partnership to enhance university education is well-established internationally, it is still an emerging field in Australia where most of such initiatives involve only small numbers of students. This paper examines the opportunities and challenges for students-as-co-inquirers initiatives in Australia. Drawing on a review of the literature, a consideration of theory, and discussions with colleagues, I propose ways in which students as co-inquirers practice and research might move forward, both in Australia and globally.